Korelasi Antara Kepercayaan Diri, Efikasi Diri, Dan Kemampuan Berbicara - Zulkarnain, Zulkarnain; Astuti, Nia; Widiati, Bidarita (Balai Diklat Keagamaan Surabaya, 2023)
The objectives of the study were to investigate the correlation between second-grade students’ self-confidence, self-efficacy and their speaking ability at the MA Miftahul Ishlah. This study applied a quantitative method with a correlational research design. The questionnaire and documentation were applied as the instrument to collect the students’ data. There were two questionnaires that were used, that was students’ self-confidence and students’ self-efficacy questionnaire, while students’ speaking score was taken from English teachers’ document. Based on the questionnaire the highest result of the self-confidence questionnaire was 97 and the lowest was 71, while the highest result of the self-efficacy questionnaire was 94 and the lowest was 72, for speaking achievement the highest result was 95 and the lowest was 70. After analyzing the variable of this research X1 (self-confidence) X2 (self-efficacy) and Y (speaking) by Pearson Product Moment and multiple correlations in the SPSS program, it was found r = .693 for correlation between students’ self-confidence with speaking and self-confidence with self-efficacy, and r = .230 for students’ self-efficacy with speaking. While the multiple correlation score showed r = .701 with a coefficient determination of 46.1%. Based on that result, it was indicated that the correlation was strong, so the alternative hypothesis stating that Ho was rejected and Ha was accepted, it means there was a correlation between students’ self-confidence, self-efficacy and speaking ability.